IMPLEMENTASI PROGRAM BERAS MISKIN DI WILAYAH KELURAHAN PUDAKPAYUNG, KECAMATAN BANYUMANIK, KOTA SEMARANG - Dian Prayoga Nugraha; R. Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
This research uses qualitative research methods. This study will describe and analyze the implementation of the programme in the region of Poor Rice Village Pudakpayung, Kecamatan Banyumanik, Semarang and its determinants of success that influenced them. This policy refers to government regulation Number 68 in 2002 about food security. Data collection techniques are in use through interviews, observation and documentation of information. The theory used is public policy implementation theory of George c. Edawrds III. The results of this research show that the implementation of the programme, Poor Neighborhood in an area of Rice Pudakpayung, Kecamatan Banyumanik, Semarang city is still less than optimal. Indicators are considered still lacking such a policy has not been an effort on target, the acceptance of the rice community that does not correspond to the number of supposed, the availability of resources is still lacking, target recipients who are not on target. The advice given was the necessity held repeated logging to collect socio-economic data, it is necessary diadakanya a profound communication in each line, the extension of poor rice, improve the quality of the rice distributed Government, needs to be fixed in the grant of facilities that have been provided, need to be added to his personnel in helping poor rice distribution.